The Correlation Between the Students’ Past Tense Mastery and Their Ability in Translating Narrative Texts - Marita Safitri (International Conference on Education and Language (ICEL), 2014)
Most students got confused and difficulty when translating from Indonesian into English. They were confused to useactive voice or passive voice in past tense to state past activities. Therefore, to solve the problem they needed to be trained to use past tense regularly. One of the ways was by asking them to translate Indonesian narrative texts into English. The objective of this research was to find out the correlation between the students’ past tense mastery and their ability in translating narrative texts of grade eleven students of SMAN 1 Pagelaran. Two kinds of tests were administered. They were grammatical test and translation test. In the grammatical test, multiple choice tests were used, while in translation test, each student was asked to translate a kind of narrative text into English.  The method of this research was the correlational research. Data were analyzed using r-Product Moment. The result of was 0.772. The p-value in 5% was 0.355 and in 1% was 0.456. So, the result showed that there was a significant correlation between the students’ past tense mastery and their ability in translating narrative texts of grade eleven students of SMAN 1 Pagelaran. Based on the result of the research, it was important both for the English teachers and the students to realize one of the factors that gave positive contribution to the students’ ability in translating narrative texts was their past tense mastery.